2018
DOI: 10.25134/ieflj.v4i1.886
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Teacher and Students Talk in Indonesian Efl Classroom Interaction

Abstract: This research analyzes teacher and students talk in Indonesian EFL classroom interaction in University of Kuningan in second semester who are taking Speaking 2 subject. This qualitative data was from observation, note taking, and interview. The result of classroom observation found the content cross as the most dominant characteristic in teacher and students talk, it means that most of the teaching learning process devoted to asking questions and lecturing by the lecturer. The proportation of content cross was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The researcher found that the largest portion of questions asked in the classroom were display questions rather than referential questions. Meida and Fadhly (2018) analyzed teacher and students' talk in a speaking class in a university level in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher found that the largest portion of questions asked in the classroom were display questions rather than referential questions. Meida and Fadhly (2018) analyzed teacher and students' talk in a speaking class in a university level in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, studies on teacher talk also gained some attention from researchers, and studies from various research settings had been done, such as; in the primary schools (Pujiastuti, 2013;Kristianingsih, 2011), in junior and senior high schools (Febiarachmah & Susanto, 2017;Pangesti, 2016;Nasir, Yusuf, & Wardana, 2019) and even in universities (Meida & Fadhly, 2018;Sofyan & Mahmud, 2014). The results slightly varied between the three different settings.…”
mentioning
confidence: 99%